Penerapan Activity-Based Costing pada Biaya Pendidikan: Sintesa terhadap Literatur - Tiara Putrirury Alamanda; Aristanti Widyaningsih; Denny Andriana (AKUNTANSI 45, 2025)
This study aims to explore pricing strategies adopted by micro, small, and medium enterprises (MSMEs) in the beauty service sector, focusing on a case study of A&S Derma Clinic in Palu City. Employing a qualitative approach with a phenomenological method, the research delves into managerial experiences in formulating pricing not solely based on cost calculations or market rates, but also grounded in customer perceived value, community purchasing power, and business sustainability. The findings reveal that a value-based pricing strategy serves as the primary approach, wherein prices are aligned with the benefits perceived by clients. A&S Derma Clinic demonstrates adaptive responses to the community’s economic conditions by offering discounts and accessible services. Moreover, pricing is strategically positioned as a tool to support long-term business stability. These insights underscore that pricing strategies within MSMEs encompass not only economic considerations but also reflect social and emotional dimensions that significantly influence overall business success.